Comprehensive PBPK Model of Rifampicin for Quantitative Prediction of Complex Drug‐Drug Interactions: CYP3A/2C9 Induction and OATP Inhibition Effects. (5th February 2018) - Asaumi, Ryuta; Toshimoto, Kota; Tobe, Yoshifusa; Hashizume, Kenta; Nunoya, Ken‐ichi; Imawaka, Haruo; Lee, Wooin; Sugiyama, Yuichi
Abstract : This study aimed to construct a physiologically based pharmacokinetic (PBPK) model of rifampicin that can accurately and quantitatively predict complex drug‐drug interactions (DDIs) involving its saturable hepatic uptake and auto‐induction. Using in silico and in vitro parameters, and reported clinical pharmacokinetic data, rifampicin PBPK model was built and relevant parameters for saturable hepatic uptake and UDP‐glucuronosyltransferase (UGT) auto‐induction were optimized by fitting. The parameters for cytochrome P450 (CYP) 3A and CYP2C9 induction by rifampicin were similarly optimized using clinical DDI data with midazolam and tolbutamide as probe substrates, respectively. For validation, our current PBPK model was applied to simulate complex DDIs with glibenclamide (a substrate of CYP3A/2C9 and hepatic organic anion transporting polypeptides (OATPs)). Simulated results were in quite good accordance with the observed data. Altogether, our constructed PBPK model of rifampicin demonstrates the robustness and utility in quantitatively predicting CYP3A/2C9 induction‐mediated and/or OATP inhibition‐mediated DDIs with victim drugs.